Relações entre a Linguagem Oral e a Linguagem Escrita - Borges, Selma Cardoso (2009)
This research intends to analyse relationships between oral language and written language in 80 children of the first and second grades. To do so, instruments of oral language assessment, that incorporate the Battery of Neuropsychology Assessment of Coimbra (Phonological Awareness, Rapid Naming and Instructions’ Comprehension), and writing and reading tasks of the Labling and PAL-Port have been used. Phonological Awareness revealed a strong association with several measures of reading and writing performance, with particular emphasis on the first grade of school. On the other hand, Rapid Naming showed more relevance on the second grade. Comparatively to the previous measures, Instructions’ Comprehension revealed to be less associated with writing and reading.